2015
DOI: 10.14814/phy2.12539
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature on apoptosis and adipogenesis on skeletal muscle satellite cells derived from different muscle types

Abstract: Satellite cells are multipotential stem cells that mediate postnatal muscle growth and respond differently to temperature based upon aerobic versus anaerobic fiber-type origin. The objective of this study was to determine how temperatures below and above the control, 38°C, affect the fate of satellite cells isolated from the anaerobic pectoralis major (p. major) or mixed fiber biceps femoris (b. femoris). At all sampling times, p. major and b. femoris cells accumulated less lipid when incubated at low temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 66 publications
5
36
1
2
Order By: Relevance
“…Decreasing the temperature of cultured satellite cells cells by 5°C under normal 37°C culture conditions reduces their proliferation rate, but also decreases apoptosis, or programmed cell death 54 . In rats subjected to an ischemia/reperfusion muscle injury, cryotherapy applied three hours after the injury reduces neutrophil accumulation and reactive oxygen species formation, and enhances the metabolic function of mitochondria 55 .…”
Section: Therapeutic Interventions For the Treatment Of Skeletal Muscmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreasing the temperature of cultured satellite cells cells by 5°C under normal 37°C culture conditions reduces their proliferation rate, but also decreases apoptosis, or programmed cell death 54 . In rats subjected to an ischemia/reperfusion muscle injury, cryotherapy applied three hours after the injury reduces neutrophil accumulation and reactive oxygen species formation, and enhances the metabolic function of mitochondria 55 .…”
Section: Therapeutic Interventions For the Treatment Of Skeletal Muscmentioning
confidence: 99%
“…In a rat muscle crush-injury model, however, reducing the temperature of muscle by 12°C for 20 minutes after inducing the injury results in reduced inflammation in the acute phase, but delayed muscle regeneration in the long term 56 . When muscle stem cells are warmed by 5°C over their normal 37°C temperature in vitro, their proliferation rate is increased, but so is the amount of apoptosis 54 . In muscle cells cultured from chicks, the application of therapeutic ultrasound in vitro results in elevated progenitor cell proliferation and an increase in the size of differentiated myotubes 57 .…”
Section: Therapeutic Interventions For the Treatment Of Skeletal Muscmentioning
confidence: 99%
“…Accumulation of lipid droplets was noticed shortly upon heat stress of cultured SCs (Harding et al, 2015;Clark et al, 2017), in SCs derived from heat-treated chicks (Piestun et al, 2017), and later, as the cells underwent differentiation, in myotubes and myofibers. The lipid accumulation was due to the induction of adipogenic gene and protein expression in the SCs (Harding et al, 2015;Clark et al, 2017;Piestun et al, 2017;Patael et al, 2019), suggesting transdifferentiation of these cells to the adipogenic lineage. Interestingly, these SCs did not seem to lose their myogenic characteristics completely, and along with the fat deposition, they underwent terminal differentiation to myotubes and fusion to myofibers.…”
Section: Negative Effects Of Thermal Stress On Sc Myogenesis In Posthmentioning
confidence: 99%
“…Detailed studies on cultured SCs from broilers (Harding et al, 2015(Harding et al, , 2016 and turkeys (Clark et al, 2016(Clark et al, , 2017 revealed that the pectoralis muscle, in particular, is highly sensitive to temperature changes. Yet, a decline in SCs did not result from increased apoptosis in either cultured cells (Harding et al, 2015) or the treated chicks (Patael et al, 2019). A surprising finding was that the heat stress caused dramatic changes in SC fate toward adipogenesis and in muscle structure toward myopathy.…”
Section: Negative Effects Of Thermal Stress On Sc Myogenesis In Posthmentioning
confidence: 99%
See 1 more Smart Citation